A Monte-Carlo study to assess the effect of 1.5 T magnetic fields on the overall robustness of pencil-beam scanning proton radiotherapy plans for prostate cancer. (19th October 2017) - Kurz, Christopher; Landry, Guillaume; Resch, Andreas F; Dedes, George; Kamp, Florian; Ganswindt, Ute; Belka, Claus; Raaymakers, Bas W; Parodi, Katia
Abstract: Combining magnetic-resonance imaging (MRI) and proton therapy (PT) using pencil-beam scanning (PBS) may improve image-guided radiotherapy. We aimed at assessing the impact of a magnetic field on PBS-PT plan quality and robustness. Specifically, the robustness against anatomical changes and positioning errors in an MRI-guided scenario with a 30 cm radius 1.5 T magnetic field was studied for prostate PT. Five prostate cancer patients with three consecutive CT images ( CT1-3 ) were considered. Single-field uniform dose PBS-PT plans were generated on the segmented CT1 with Monte-Carlo-based treatment planning software for inverse optimization. Plans were optimized at 90° gantry angle without B-field ( no B ), with  ±1.5 T B-field ( B and minus B ), as well as at 81° gantry angle and  +1.5 T ( B G81 ). Plans were re-calculated on aligned CT2 and CT3 to study the impact of anatomical changes. Dose distributions were compared in terms of changes in DVH parameters, proton range and gamma-index pass-rates. To assess the impact of positioning errors, DVH parameters were compared for  ±5 mm CT1 patient shifts in anterior–posterior (AP) and left–right (LR) direction. Proton beam deflection considerably reduced robustness against inter-fractional changes for the B scenario. Range agreement, gamma-index pass-rates and PTV V95% were significantly lower compared to no B . Improved robustness was obtained for minus B and B G81, the latter showing only minor differences to no B . The magnetic field introduced slight dosimetric changes under LR shifts. The impact of AP shifts was considerably larger, and equivalent for scenarios with and without B-field. Results suggest that robustness equivalent to PT without magnetic field can be achieved by adaptation of the treatment parameters, such as B-field orientation ( minus B ) with respect to the patient and/or gantry angle ( B G81 ). MRI-guided PT for prostate cancer might thus be implemented without compromising robustness compared to state-of-the-art CT-guided PT.